Knowledge risk and its mitigation : practices and cases - Lee, Rongbin W. B.; Yip, Jessica Y. T.; Shek, Vivien W. Y. (Bingley, U.K. : Emerald Publishing Limited, 2021)
The life cycle of companies and enterprises, at present, is short-lived due to rapid social and technological changes. Despite the growing awareness on the importance of knowledge management (KM) among academic researchers, it is still not widely practiced in industry. Why is this? Most KM programs emphasize the importance of capturing, retaining, and sharing organisational knowledge amongst their stakeholders. The beneficial effect of these programs is rarely felt immediately, which often results in senior management avoiding prioritising KM initiatives. To overcome this hurdle in implementing KM an approach that includes the assessment of knowledge risk factors and the disastrous effect on the daily operation of the company is explored. This book is the first attempt of its kind to provide a pragmatic view to launch knowledge risk management at the grassroot level, with steps by steps on what should be the mission and practical skills needed for a KM practitioner. Another surprise of this book is the numerous cases, examples and data that are brough about from the real business world. For business practitioners, KM researchers and those in HR, risk management, management accounting and Leadership this work is a must for expanding their understanding of Knowledge Management and knowledge risks.
Chapter 1. Introduction -- Chapter 2. Assessment of knowledge risks -- Chapter 3. Intellectual capital charting, accounting and risks -- Chapter 4. Knowledge audit -- Chapter 5. Knowledge elicitation for unstructured business process -- Chapter 6. Building a learning organization -- Chapter 7. KM implementation -- Chapter 8. Measuring corporate performance.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Risk management; Knowledge management; Business & Economics -- Knowledge Capital; Knowledge management